Comparative cost models of a liquid nitrogen vapor phase (LNVP) cold chain-distributed cryopreserved malaria vaccine vs. a conventional vaccine - Garcia, Cristina Reyes (2012)
Typically, vaccines distributed through the Expanded Program on Immunization (EPI) use a 2–8 °C cold chain with 4–5 stops. The PfSPZ Vaccine comprises whole live-attenuated cryopreserved sporozoites stored in liquid nitrogen (LN(2)) vapor phase (LNVP) below −140 °C and would be distributed through a LNVP cold chain. The purpose of this study was to model LNVP cold chain distribution for the cryopreserved PfSPZ Vaccine in Tanzania, estimate the costs and compare these costs to those that would be incurred in distributing a ‘conventional’ malaria vaccine through the EPI. Capital and recurrent costs for storage, transportation, labor, energy usage and facilities were determined for the birth cohort in Tanzania over five years. Costs were calculated using WHO/UNESCO calculators. These were applied to a 2–8 °C distribution model with national, regional, district, and health facility levels, and for the cryopreserved vaccine using a ‘modified hub-and-spoke’ (MH-S) LNVP distribution system comprising a central national store, peripheral health facilities and an intermediate district-level transhipment stop. Estimated costs per fully immunized child (FIC) were $ 6.11 for the LNVP-distributed cryopreserved vaccine where the LN(2) is generated, and $ 6.04 with purchased LN(2) (assuming US $ 1.00/L). The FIC costs for distributing a conventional vaccine using the four level 2–8 °C cold chain were $ 6.10, and with a tariff distribution system as occurs in Tanzania the FIC cost was $ 5.53. The models, therefore, predicted little difference in 5-year distribution costs between the PfSPZ Vaccine distributed through a MH-S LNVP cold chain and a conventional vaccine distributed through the more traditional EPI system. A LNVP cold chain provides additional benefits through the use of durable dry shippers because no refrigerators, freezers or refrigerated trucks are required. Thus strain at the cold chain periphery, vaccine wastage from cold chain failures and the environmental impact of distribution would all be reduced.